Monitoring cell and tissue damage during ablation by high-intensity focussed ultrasound - Nandlall, S; Sacha Nandlall (2011)
High Intensity Focussed Ultrasound (HIFU) ablation is a promising technology for the non-invasive, targeted treatment of certain types of cancer. The technique functions by subjecting tumours to a cytotoxic level of intense, localised heating, while leaving the surrounding tissue unharmed. However, a number of limitations in the available HIFU treatment monitoring methods are currently hampering the effectiveness and clinical adoption of the therapy. This work aims to develop improved metrics of HIFU-induced biological damage that are specifically suited to monitoring and controlling HIFU ablation. Firstly, an optical method that enables straightforward quantification of thermal damage in protein-embedding hydrogels is developed. Secondly, hydrogels embedded with different cell lines are used to assess the performance of common temperature-based metrics of cell death across a range of HIFU-relevant conditions. Finally, a novel, passive acoustic detector designed for the real-time monitoring of HIFU-induced tissue damage is proposed. The detector is shown to predict lesioning with over 80% accuracy in regimes that are very likely to create lesions (60 J of acoustic energy or more), with an error rate of less than 6% for exposures that are too short to cause lesioning (up to 1 s long). The proposed detector could therefore provide a low-cost means of effectively monitoring clinical HIFU treatments passively and in real time.